Experience Adaptation of Adolescent Post-Disaster Disasters in the Lombok Nusa Tenggara Barat - Anika, Nova; Yusuf, Ah; Tristiana, Rr Dian (Psychiatry Nursing Journal (Jurnal Keperawatan Jiwa), 2019)
Introduction: Disaster events can cause harm from physical, psychological, property and environmental aspects. Disasters affect the psychological well-being and mental health of individuals, both adults and children and adolescents. Post-disaster adaptation process is needed to achieve an adaptive response for adolescents so that post-traumatic stress does not become pathological. The purpose of this study was to explore the experiences of adolescent adaptation after the earthquake disaster in Lombok West Nusa Tenggara in 2018.Method: This study used phenomenological qualitative research methods with in-depth interviews with 18 adolescents affected by the earthquake disaster, Analysis of data used refers to nine steps colaizzi data analysis techniques.Results: the results of this study obtained 11 themes: 1) changes in how to socialize, 2) changes in roles, 3) Exploring other abilities 4) Response to earthquakes, 5) Efforts to overcome the impact of disasters, 6) Sources of Support, 7) Types of Support, 8) Meanings of disasters, 9) Expectations for Lombok, 10) Expectations for oneself, 11) Expectations for authorities.Conclusion: Efforts to deal with the effects of earthquakes or coping strategies used by adolescents in the form of spiritual changes and distractions. Get closer to God by doing various forms of worship in accordance with the religion that is followed has an important role to be able to adapt to the impact caused by the earthquake disaster in adolescents.